Fourier spectroscopy of water vapor in the volume of aerogel nanopores. Part 2. Calculation of broadening and shift of spectral lines by adsorbed molecules; Atmospheric and Oceanic Optics; Vol. 28, iss. 3 - Solodov A. M. Aleksandr Mikhaylovich; Petrova T. M. Tatjyana Mikhaylovna; Solodov A. A. Aleksandr Aleksandrovich; Starikov V. I. Vitaly Ivanovich (Spectroscopy of ambient medium, 2015)
Title screen